A novel indoor channel model for tvws communications based on measurements - Hashir, Syed Muhammad; Erküçük, Serhat; Baykaş, Tunçer (Institute of Electrical and Electronics Engineers Inc., 2018)
In this paper, we present an indoor measurement campaign for TV white space bands inside a university building. The measurement results are compared with different indoor propagation models in the literature. We observed large estimation errors for the total path loss value from all existing models. Consequently, we are proposing a new indoor propagation model for TVWS frequencies, which concatenates the effects of frequency dependent path loss with penetration losses due to walls and windows. Performance comparison with existing models show that the proposed model achieves superior performance compared to existing models in terms of Root-Mean-Squared Error (RMSE).
Keywords: Indoor Propagation Model; Measurement; Spectrum Sharing Systems; TV white space; TVWS